REDESAIN GEDUNG PERPUSTAKAAN DAERAH TOBELO DENGAN MEMBANDINGKAN EFISIENSI KOLOM PERSEGI DAN KOLOM BULAT : (Perbandingan Kekuatan Kolom) - Kefas V. T. Hendrik; N.A.R.A Mamarimbing; Jeffrey A. Delarue, (Sustainable Construction (SUSCON), 2023)
The development era in Indonesia is increasing, especially in the Tobelo area, North Maluku province, where in general, the construction of multi-story building structures in the Tobelo area, such as; places of worship, offices, shops, homes, and so on. It is rare to find a building that uses a round column design as the main structure of a building but prefers to use a rectangular column design as the main structure in a building. This is the background of this research to determine the comparison of strength levels between square columns and round columns. The analysis process in this study used the SAP2000 V22 program with a rectangular column cross-sectional size of 60 x 60 cm and a circular column cross-sectional length of 67 cm in diameter. The calculation of the strength of the two columns produces a power that can be supported by a rectangular column namely Pu = 7,838.1841 Kn and Mu = 945.82303 Kn.m, and the strength that can be supported by a round column, namely Pu = 7,711.7932 Kn and Mu = 942.22566 Kn.m, thus the two columns have almost the same power.